Credibility Contests: Media Debates on Do-It-Yourself Coronavirus Responses and the Role of Citizens in Health Crises - Erikainen, Sonja; Stewart, Ellen (Frontiers in Sociology, 2020)
During the early months of the COVID-19 pandemic in Europe and North America, news outlets ran a series of stories reporting on “do-it-yourself” (DIY) coronavirus responses that were created and implemented by citizens. This news discourse exemplifies and can illuminate wider shifts in the roles of citizens in science, as individual outside professional science institutions are becoming more actively involved in scientific knowledge production than before, while the epistemic authority of professional “expert” scientists has been increasingly contested. This paper takes news discourses on DIY coronavirus responses as a lens to explore wider questions around the changing ways in which the roles of different public health actors are delineated and represented under conditions of significant social and epistemic uncertainty. We aim to shed new light on the nature of – and the role of the news media in mediating – the credibility contests and boundary work that is currently at play around citizen participation in science and innovation. We do so by focusing on four discourses: polarised discourses around DIY face masks and hand sanitisers; delineation of credible from incredible interventions and actors around DIY coronavirus treatments and tests; delineation of professional science from “fringe” citizen science; and discourses declaring that “we’re all in this together.” We conclude that making sense of these discourses requires a thorough appreciation of the context in which they emerged. Our analysis reveals how emancipatory accounts of the DIY science can mask structural inequalities underlying who can and is expected to “do-it-themselves,” and how.